1998
DOI: 10.1038/23968
|View full text |Cite
|
Sign up to set email alerts
|

NMR structure of the histidine kinase domain of the E. coli osmosensor EnvZ

Abstract: Bacteria live in capricious environments, in which they must continuously sense external conditions in order to adjust their shape, motility and physiology. The histidine-aspartate phosphorelay signal-transduction system (also known as the two-component system) is important in cellular adaptation to environmental changes in both prokaryotes and lower eukaryotes. In this system, protein histidine kinases function as sensors and signal transducers. The Escherichia coli osmosensor, EnvZ, is a transmembrane protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
218
0
7

Year Published

2003
2003
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 253 publications
(230 citation statements)
references
References 18 publications
5
218
0
7
Order By: Relevance
“…The C-terminal cytoplasmic domain is organized into a four-helix bundle subdomain, with two helices being contributed by each monomer and linked to the ATP-binding kinase subdomain through a flexible linker. Structures of the four-helix bundle (PDB: 1JOY) (19) and the kinase subdomains (PDB: 1BXD) (20) solved by NMR offered structural insights into the isolated subdomains at low osmolality. Crystallographic structures of the two subdomains tethered together were solved recently in a chimeric construct of EnvZ formed from Thermotoga maritima and Escherichia coli EnvZ (PDB: 4KP4) (21), representing the structure of EnvZ at high osmolality (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…The C-terminal cytoplasmic domain is organized into a four-helix bundle subdomain, with two helices being contributed by each monomer and linked to the ATP-binding kinase subdomain through a flexible linker. Structures of the four-helix bundle (PDB: 1JOY) (19) and the kinase subdomains (PDB: 1BXD) (20) solved by NMR offered structural insights into the isolated subdomains at low osmolality. Crystallographic structures of the two subdomains tethered together were solved recently in a chimeric construct of EnvZ formed from Thermotoga maritima and Escherichia coli EnvZ (PDB: 4KP4) (21), representing the structure of EnvZ at high osmolality (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…The cytoplasmic domain has been further dissected into three subdomains, the linker region, domain A, and domain B, in which the latter two form the catalytic core of EnvZ, harboring both kinase and phosphatase functions (3). NMR structures of both domain A and domain B have been solved (4,5). Biochemical analysis has revealed that the domain A of the EnvZ is responsible for the dimerization, phosphotransfer and phosphatase functions, and domain B binds ATP and catalytically assists the enzymatic function of domain A (3,6).…”
mentioning
confidence: 99%
“…If FeuQ has both kinase and phosphatase activities, we hypothesized that selective elimination of kinase activity by mutation would create dominantnegative variants due to unchecked phosphatase activity. This is consistent with observations in other bifunctional sensor kinases (Atkinson & Ninfa, 1993;Hsing & Silhavy, 1997;Tanaka et al, 1998). To test this hypothesis, we created two FeuQ variants that were predicted to eliminate kinase activity while potentially leaving phosphatase activity intact.…”
Section: Does the Feun/q Interaction Cause An Increase In Feuq Phosphmentioning
confidence: 49%
“…An identical mutation in the well-characterized SK EnvZ was shown to eliminate kinase but not phosphatase activity (Hsing & Silhavy, 1997). Another variant, FeuQ (G398A), changes a highly conserved Gly residue previously shown to be critical for ATP binding and autophosphorylation (Tanaka et al, 1998). In the experiment shown in Fig.…”
Section: Does the Feun/q Interaction Cause An Increase In Feuq Phosphmentioning
confidence: 96%